2019
DOI: 10.1109/access.2019.2947449
|View full text |Cite
|
Sign up to set email alerts
|

An Umbrella-Shaped Linear Piezoelectric Actuator Based on Stick-Slip Motion Principle

Abstract: Piezoelectric actuators are widely utilized in many research and industrial fields, since they could achieve high positioning accuracy based on inverse piezoelectric effect. However, the working stroke of piezoelectric actuators is always limited, which restricts the further application of piezoelectric actuators. In order to solve this problem on short working stroke, this study introduces an umbrella-shaped linear piezoelectric actuator to achieve a large working stroke. Unlike traditional stick-slip actuato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…To improve the consistency of FHMs-PSSAs forward and reverse performance, some FHMs-PSSAs adopted the structural design that two asymmetric stators were directly connected in parallel type (Huang et al, 2020; Li et al, 2017a, 2018a; Wang et al, 2019a; Yang et al, 2020b) or in series type (Huang et al, 2012) on the mechanical mechanism; however, due to the normal pressure between the two driving feet and the slider, the other stationary driving foot adversely affected the driving performance as one driving foot was driving. To avoid the above interference phenomenon, although the two driving units were in series (Wang et al, 2019b, 2020b) or parallel (Chu et al, 2016; Liu et al, 2012; Lu et al, 2020a; Wang et al, 2011; Yao et al, 2019; Zhang et al, 2019c) structures, they shared one driving foot by decoupling design, as shown in Figure 10(a) and (b). In addition, the two driving units could be designed into a centrosymmetric mechanism as well (Qin et al, 2019b), the adjusted objects install on the two sliders respectively, and the relative positions between the two objects could be adjusted by the actuator, see Figure 10(c).…”
Section: Improvement Of Fhms-pssasmentioning
confidence: 99%
“…To improve the consistency of FHMs-PSSAs forward and reverse performance, some FHMs-PSSAs adopted the structural design that two asymmetric stators were directly connected in parallel type (Huang et al, 2020; Li et al, 2017a, 2018a; Wang et al, 2019a; Yang et al, 2020b) or in series type (Huang et al, 2012) on the mechanical mechanism; however, due to the normal pressure between the two driving feet and the slider, the other stationary driving foot adversely affected the driving performance as one driving foot was driving. To avoid the above interference phenomenon, although the two driving units were in series (Wang et al, 2019b, 2020b) or parallel (Chu et al, 2016; Liu et al, 2012; Lu et al, 2020a; Wang et al, 2011; Yao et al, 2019; Zhang et al, 2019c) structures, they shared one driving foot by decoupling design, as shown in Figure 10(a) and (b). In addition, the two driving units could be designed into a centrosymmetric mechanism as well (Qin et al, 2019b), the adjusted objects install on the two sliders respectively, and the relative positions between the two objects could be adjusted by the actuator, see Figure 10(c).…”
Section: Improvement Of Fhms-pssasmentioning
confidence: 99%
“…A bender-type PEA combines bending PEAs and extending PEAs using the bonding layer that absorbs internal stress, and this bonding layer increases flexibility of bender-type PEAs. Each bender-type PEAs on the top arranged along counterclockwise are named as [1], [2], [3] and [4] respectively. Correspondingly, each PEAs on the bottom are separately labeled as…”
Section: Structure Of Inchworm Piezo Motormentioning
confidence: 99%
“…Piezoelectric actuators (PEAs) are transducers producing a mechanical displacement in response to an applied voltage based on an inverse piezoelectric effect [1,2]. Given their nano-precision displacement, rapid response, and high positioning accuracy [3,4], PEAs are widely used in the fields * Author to whom any correspondence should be addressed. of super-resolution microscopy for semiconductor tests [5], ultra-precision micro-machines for manufacturing [6] and micro-robots for joint compensation technology [7].…”
Section: Introductionmentioning
confidence: 99%
“…The high-speed motion performance of the resonant type is superior, but the problems of wear and heat are still to be solved [17,18]. Compared with the inchworm type, the structure of the stick-slip type is relatively simple and easy to control, but its output performance is weak [19,20].…”
Section: Introductionmentioning
confidence: 99%